Studies on Biochemical Changes in the Fish Ctenopharyngodon idella in Relation to Arsenic Toxicity - Mathivanan, V (International Journal of Pharmaceutical & Biological Archive, 2014)
Studies on Biochemical Changes in the Fish Ctenopharyngodon idella in Relation to Arsenic Toxicity